COMPARISON OF VEGETARIANS AND NON-VEGETARIANS IN BODY MASS INDEX INDICATORS AND CHOLESTEROL LEVELS - Helen Sabatini Simbolon, Yunus Elon (JOURNAL of HEALTH SCIENCE REVIEW, 2024)
Background: Nutritional status of adults can be seen simply by using body mass index, and especially nutritional status related to vegetarian and nonvegetarian dietary status.Objective: This study aimed to assess the cholesterol levels and BMI of Adventist University Indonesia students. Methods: Using Spearman's rho test, this research technique is quantitative. There were 60 participants who voluntarily gave their consent. The tool used in this study is a lipid profile (measuring tool for cholesterol levels), Results: the study showed that there was no relationship between gender and BMI. While there is a significant relationship to dietary status and cholesterol levels with a unidirectional positive value (p = .000 r = .578).